Sectoral Efficiency Level in Yogyakarta Province - Fikriya, Elkhana; Fafurida, Fafurida (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this study is to determine the level of efficiency, level of inefficiency and solutions that need to be done to improve the efficiency of each sector in the Yogyakarta Province. This research is a quantitative research with Data Envelopment Analysis (DEA) approach banxia frontier analysis. Variable used in this research is variable input (labor and investment), and output variable (GRDP). The data used are secondary data for the period 2012 – 2016 from the Central Bureau Statistic. The research objects include main occupational sectors in Yogyalarta Province. The results of this study show that from nine sectors in DI Yogyakarta Province there are six sectors inefficient, namely the agricultural sector ; mining and quarrying; processing industry; electricity, gas and water; Large trade; and other services during 2012 - 2016. Three of the nine sectors namely the construction sector; transport; and finance reached 100% efficiency during 2012 - 2016. Sectoral inefficiency occurs because the combination of the varabel quantity of the input is not appropriate, so it needs to be adjusted input factor quantity in order to produce the output efficiently 100%. The conclusion of this study shows the efficiency of sectoral techniques in the Province of Yogyakarta in the tendency of low efficiency which decreases each year. Based on the results of the study the authors suggest six of the nine sectors that have not achieved 100% efficiency rating need to adjust the amount of input factor value in order to achieve ouput efficiently 100%. Tujuan penelitian ini adalah untuk mengetahui tingkat efisiensi, tingkat inefisiensi serta solusi yang perlu dilakukan untuk meningkatkan efisiensi tiap sektor di Provinsi DI Yogyakarta. Penelitian ini merupakan penelitian kuantitatif dengan metode Data Envelopment Analysis (DEA) pendekatan banxia frontier analysis.Variabel yang digunakan dalam penelitian ini adalah variabel input (tenaga kerja dan investasi), dan variabel output (PDRB). Data yang digunakan adalah data sekunder periode tahun 2012 – 2016. Dari Badan Pusat Statistik. Adapun objek penelitian meliputi sembilan sektor pekerjaan utama di Provinsi DI Yogyakarta. Hasil penelitian ini menunjukan bahwa dari sembilan sektor di Provinsi DI Yogyakarta terdapat enam sektor yang inefisien yakni sektor pertanian; pertambangan dan penggalian; industri pengolahan; listrik, gas, dan air; perdagangan besar; dan jasa lainnya selama tahun 2012 – 2016. Tiga dari sembilan sektor yakni sektor konstruksi; angkutan; dan keuangan mencapai efisien 100% selama tahun 2012 – 2016. Inefisiensi sektoral terjadi karena pengkombinasian besaran varabel input yang tidak sesuai, sehingga perlu dilakukan penyesuaian besaran faktor input dalam rangka menghasilkan output secara efisien 100%. Kesimpulan dari penelitian ini menunjukkan efisiensi teknik sektoral di Provinsi DI Yogyakarta kecenderungan efisiensi rendah yang menurun tiap tahunnya. Berdasarkan hasil penelitian penulis menyarankan enam dari sembilan sektor yang belum mencapai nilai efisiensi 100% perlu melakukan penyesuaian besaran nilai faktor input dalam rangka mencapai ouput secara efisien 100%.